Reduced indinavir exposure during pregnancy - Tim R. Cressey (2018)
Aim: To describe the pharmacokinetics and safety of indinavir boosted with ritonavir (IDV/r) during the second and third trimesters of pregnancy and in the post-partum period. Methods: IMPAACT P1026s is an on-going, prospective, non-blinded study of antiretroviral pharmacokinetics (PK) in HIV-infected pregnant women with a Thai cohort receiving IDV/r 400/100mg twice daily during pregnancy through to 6-12 weeks post-partum as part of clinical care. Steady-state PK profiles were performed during the second (optional) and third trimesters and at 6-12 weeks post-partum. PK targets were the estimated 10thpercentile IDV AUC (12.9μgml-1h) in non-pregnant historical Thai adults and a trough concentration of 0.1μgml-1, the suggested minimum target. Results: Twenty-six pregnant women were enrolled; thirteen entered during the second trimester. Median (range) age was 29.8 (18.9-40.8) years and weight 60.5 (50.0-85.0) kg at the third trimester PK visit. The 90% confidence limits for the geometric mean ratio of the indinavir AUC(0,12h) and Cmaxduring the second trimester and post-partum (ante:post ratios) were 0.58 (0.49, 0.68) and 0.73 (0.59, 0.91), respectively; third trimester/post-partum AUC(0,12h) and Cmaxratios were 0.60 (0.53, 0.68) and 0.63 (0.55, 0.72), respectively. IDV/r was well tolerated and 21/26 women had a HIV-1 viral load < 40 copies ml-1at delivery. All 26 infants were confirmed HIV negative. Conclusion: Indinavir exposure during the second and third trimesters was significantly reduced compared with post-partum and ∼30% of women failed to achieve a target trough concentration. Increasing the dose of IDV/r during pregnancy to 600/100mg twice daily may be preferable to ensure adequate drug concentrations. © 2013 The Authors.